OPTIMIZATION OF THE CALCULATION OF SYNCHRONOUS RELUCTANCE MOTOR FOR A COAL HARVESTER 180 KW - Єгоров, Олексій; Єгорова, Ольга; Глєбова, Марина; Форкун, Яна (SWorldJournal, 2024)
Three-phase induction motors are the most common type of motor in the mining industry, but there is currently interest in new types of IM motors, one of which is the synchronous reluctance motor (SRM).SRM are a step up from permanent magnet motors in ter